BATHYMETRICAL FEATURES OF THE BALI-LOMBOK STRAIT - Bruun, Anton F.; Kiilerich, A. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1957)
The full understanding of the distributio of the surface temperature and salinity requires the knowledge of the heat and water balance at the surface of the ocean as well as of the circulation. For southeast Asian waters the monthly averages of the climatological factors determining the heat and water balance are calculated and presented in the following for 15 regions.